Denaturing high performance liquid chromatography: high throughput mutation screening in familial hypertrophic cardiomyopathy and SNP genotyping in motor neurone disease. Issue 5 (27th April 2005) - Yu, B; Sawyer, N A; Caramins, M; Yuan, Z G; Saunderson, R B; Pamphlett, R; Richmond, D R; Jeremy, R W; Trent, R J
Abstract : Aims: To evaluate the usefulness of denaturing high performance liquid chromatography (DHPLC) as a high throughput tool in: (1) DNA mutation detection in familial hypertrophic cardiomyopathy (FHC), and (2) single nucleotide polymorphism (SNP) discovery and validation in sporadic motor neurone disease (MND). Methods: The coding sequence and intron–exon boundaries of the cardiac β myosin heavy chain gene (MYH7) were screened by DHPLC for mutation identification in 150 unrelated patients diagnosed with FHC. One hundred and forty patients with sporadic MND were genotyped for the A67T SNP in the poliovirus receptor gene. All DHPLC positive signals were confirmed by conventional methods. Results: Mutation screening of MYH7 covered 10 kb with a total of 5700 amplicons, and more than 6750 DHPLC injections were completed within 35 days. The causative mutation was identified in 14% of FHC cases, including seven novel missense mutations (L227V, E328G, K351E, V411I, M435T, E894G, and E927K). Genotyping of the A67T SNP was performed at two different temperatures both in MND cases and 280 controls. This coding SNP was found more frequently in MND cases (13.6%) than in controls (6.8%). Furthermore, 19 and two SNPs were identified in MYH7 and the poliovirus receptor gene, respectively, during DHPLC screening. Conclusions: DHPLC is a high throughput, sensitive, specific, and robust platform for the detection of DNA variants, such as disease causing mutations or SNPs. It enables rapid and accurate screening of large genomic regions.